2020
DOI: 10.1101/2020.05.21.108605
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanistic insights into ventricular arrhythmogenesis of hydroxychloroquine and azithromycin for the treatment of COVID-19

Abstract: CLHH, HZ, ML and GLH are joint senior authors Article length: 6234 words, including figure legends and references, excluding abstract and acknowledgements 3 ABSTRACT Aims:We investigate mechanisms for potential pro-arrhythmic effects of hydroxychloroquine (HCQ) alone, or combined with azithromycin (AZM), in Covid-19 management supplementing the limited available experimental cardiac safety data. Methods:We integrated patch-clamp studies utilizing In Vitro ProArrhythmia Assay (CiPA) Schema IC50 paradigms, molec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…To understand the influence of different dosages of HCQ alone and in combination with AZM in the COVID-19 infected cardiac tissue, the cardiomyocyte's ionic current parameters are varied based on the clinical study reported by Wang et al, [21], and listed in Table 3. To the best of the author's knowledge, prior art studies have not considered the role of temperature (fever) arising due to COVID-19; in this study, we configure the computational model of the ventricular tissue with an elevated temperature of 313.15 Kelvin.…”
Section: Dosage Effects In Covid-19 Infected Cardiac Tissue: Hcq and With Azmmentioning
confidence: 99%
“…To understand the influence of different dosages of HCQ alone and in combination with AZM in the COVID-19 infected cardiac tissue, the cardiomyocyte's ionic current parameters are varied based on the clinical study reported by Wang et al, [21], and listed in Table 3. To the best of the author's knowledge, prior art studies have not considered the role of temperature (fever) arising due to COVID-19; in this study, we configure the computational model of the ventricular tissue with an elevated temperature of 313.15 Kelvin.…”
Section: Dosage Effects In Covid-19 Infected Cardiac Tissue: Hcq and With Azmmentioning
confidence: 99%
“…Hydroxychloroquine was given limited emergency use authorization by the FDA in combination with azithromycin, which was subsequently revoked [249] . More recently, (hydroxy)chloroquine has been declared ineffective in numerous CoVID‐19 trials [250] . Analysis across numerous publications indicates little beneficial effect of hydroxychloroquine on CoVID‐19.…”
Section: (Hydroxy)chloroquinementioning
confidence: 99%
“…Most studies above have focused on approved drugs, although some included molecules in “preclinical” evaluation. Given the situation, preclinical molecules were unlikely to lead to a timely solution, but, we believe that focusing solely on approved drugs was likely too narrow [250] . To explain this logic, we breakdown the trials process.…”
Section: Choice Of Compounds To Be Evaluated In Rapid Screening Clinical Trialsmentioning
confidence: 99%
“…233 Analysis across numerous publications indicates little beneficial effect of hydroxychloroquine on CoVID-19. The use of hydroxychloroquine with azithromycin may actually increase mortality 249 and negative symptoms associated with both drugs. 250 Some interest remains in (hydroxy)chloroquine serving as a prophylactic treatment against CoVID-19, 251 although recent reports are not encouraging.…”
Section: Targeting Transcription: Remdesivirmentioning
confidence: 99%